Toughening of Ceramic Shell Mould with Rice Husk Fiber (CSm-RH) to Improve Strength Property and Mould Performance - Kamarudin, Noor Hasliza; Harun, Zawati; Hussain, Rosniza; Jamalludin, Mohd Riduan; Hubadillah, Siti Khadijah; Alias, Siti Salwa; Syamsul Bahri, Syamsutajri; Sazali, Nursuhailizah; Mohd Akhair, Siti Hajar (Emerging Advances in Integrated Technology, 2021)
For ages, ceramic shell mould (CSm) have been extensively applied in investment casting industry. The formation of CSm requires multiple steps of dipping, layering drying and firing stages. The later steps are very crucial as the solidification thin layer CSm that consist of loose ceramic particles easily cracks when exposed to the higher thermal effect. The inclusion of fiber or any reinforces phases is able to enhance fired ceramic body and also strengthen the green ceramic structure. Thus, the feasibility of rougher NaOH treated rice husk fiber (RHT) prior embedded into composited structure has shown a significant CSm improvement by induced a better adhesion properties and larger bonding area with brittle ceramic matrix, resulted in increased green strength (1.34 MPa) and fired body strength (4.32 MPa). Owing to the decomposed of lignin layer in CSm-RHU exhibited a higher porosity that provide a better permeation paths of air flow during molten metal pouring as increased 30 % from the standard CSm permeability, giving an enormous benefit for investment casting cooling process. Overall, the incorporation of RHT fiber in a CSm matrix of both green and fired body governed in toughening of brittle ceramic body, hence avoid failure to the casting mould.